Hepatitis B and C - Rodrigo, Luis (Infectious Diseases, 2020)
This book on Hepatitis B and C contains very useful and recent information about the general characteristics of these common types of chronic liver infections. Referred to as Hepatitis B, there are three chapters describing the main epidemiological, clinical, therapeutic, and prognosis aspects. The molecular variants for HBsAg, its genotyping, and their clinical implications are fully analyzed. The implications of coinfection Hepatitis B and C in HIV patients and their treatment are described. In relation to Hepatitis C, there are three chapters describing the general characteristics of this chronic viral infection. The challenges and strategies for access to treatment of Hepatitis C in Latin America are fully covered and these can be applied in other countries with similar epidemiological and financial problems for access to treatment on a large scale. The role of direct-acting antivirals (DAA) in the treatment of chronic Hepatitis C infection with liver cirrhosis is clearly documented.